Synthesis and antimicrobial evaluation of a novel 1,3,5-trisubstituted Pyrazole derivative - Al-Difar, H.; Darwish, K.; Baaiu, B. (Libyan Journal of Science &Technology, 2022)
A novel 1,3,5-trisubstituted pyrazole derivative was synthesized through multistep reaction. Biological screening has been made for each new product of the multistep synthesis, using a gram-positive bacterium and one fungus. Most of the synthesized compounds exhibited comparatively moderate activity against the chosen species using variable concentrations.